Social Networks across Chignecto: Applying Social Network Analysis to Acadie, Mi’kma’ki, and Nova Scotia, 1670-1751 - Kennedy, Gregory; Peace, Thomas; Pettigrew, Stephanie (Acadiensis, 2018)
This article examines the Acadian community of Beaubassin with a view to better understanding its social hierarchy and the relationships between colonists and their Mi’kmaq neighbours during the period up to 1751. Beaubassin has long been the least understood Acadian community, due in part to its distance from the colonial capital at Port Royal and also because its parish registers are not complete. However, social network analysis can provide new insights. The authors study families across generations, re-interpret a local witchcraft trial, and take a fresh look at the presence of Aboriginal peoples, determining that Beaubassin was a community of growing complexity and with stronger connections to the Mi’kmaq than previously understood.